2008
DOI: 10.1038/ncpneph1019
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury caused by intravascular hemolysis after mechanical thrombectomy

Abstract: Acute kidney injury caused by intravascular hemolysis after mechanical thrombectomy. Continuing Medical Education online Medscape, LLC is pleased to provide online continuing medical education (CME) for this journal article, allowing clinicians the opportunity to earn CME credit. Medscape, LLC is accredited by the Accreditation Council for Continuing Medical Education (ACCME) to provide CME for physicians. Medscape, LLC designates this educational activity for a maximum of 0.5 AMA PRA Category 1 Credits TM . P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 15 publications
2
55
0
4
Order By: Relevance
“…Early studies have demonstrated intravascular haemolysis following procedure with clinically insigni icant drops in Hb concentrations, elevated LDH and low haptoglobin consistent with haemolysis, and less frequently an increase in creatinine [8]. In 2009 [3] reported a presumed irst case of severe AKI requiring dialysis following AngioJet TM PMT in a patient with pulmonary embolus [3]. Prior to this in 2007, however, a prior paediatric case of AKI involving PMT had already been reported in a 16 year old patient with severe clot burden DVT and multiple administration of contrast resulting in severe AKI requiring peritoneal dialysis [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies have demonstrated intravascular haemolysis following procedure with clinically insigni icant drops in Hb concentrations, elevated LDH and low haptoglobin consistent with haemolysis, and less frequently an increase in creatinine [8]. In 2009 [3] reported a presumed irst case of severe AKI requiring dialysis following AngioJet TM PMT in a patient with pulmonary embolus [3]. Prior to this in 2007, however, a prior paediatric case of AKI involving PMT had already been reported in a 16 year old patient with severe clot burden DVT and multiple administration of contrast resulting in severe AKI requiring peritoneal dialysis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although its bene it in upper limb DVT is less clear [2], the presence of a large symptomatic thrombus prompted decision to proceed with thrombolysis and PMT in addition to anticoagulation. Targeted therapy for thrombus dissolution also remains an attractive strategy in patients with signi icant bleeding risk or where systemic thrombolysis is not an option [3]. AngioJet TM , available at our facility, creates a hydrodynamic vortex through retrogradely oriented high speed luid jets allowing selective trapping and dissolving of thrombi [4].…”
Section: Introductionmentioning
confidence: 99%
“…Intravascular haemolysis of various causes can result in acute tubular necrosis due to haemoglobinuria leading to acute renal failure (12). Our case showed no derangement in his renal function, which might because of his early presentation and degree of haemolysis.…”
Section: Discussionmentioning
confidence: 57%
“…Hyperkalemia may exacerbate the electrical instability, and hemoglobinuria may cause further deterioration of kidney function in these patients already at risk of kidney failure because of hemodynamic instability and contrast medium administered for the ART procedure with or without diagnostic computed tomography angiography (8). The placement of a temporary pacemaker wire and the aggressive control of potassium levels are crucial during the ART procedure in patients presenting with massive PE.…”
Section: Angiojet Rheolytic Thrombectomy Inmentioning
confidence: 99%